Vocabulary size and depth as predictors of second language speaking ability. (July 2021) - Janebi Enayat, Mostafa; Derakhshan, Ali
Abstract: This article investigates the contribution of vocabulary size and depth to second language (L2) speaking proficiency as well as its two dimensions of fluency and lexical resource. To this end, 46 English as a Foreign Language (EFL) learners took the Word Associates Test (WAT), Vocabulary Levels Test (VLT), Lex30, and the speaking tasks of International English Language Testing System (IELTS). Results of multivariate and ridge regression analyses indicated that (a) the three measures of vocabulary could jointly have a significant contribution to the prediction of the overall speaking ability as well as its two aspects of fluency and lexical resource; (b) receptive vocabulary size, as measured through the VLT, had a unique prediction of the overall L2 speaking proficiency; (c) receptive vocabulary depth could not predict any of the dependent variables; (d) productive vocabulary knowledge was predictive of the fluency and coherence dimension of L2 speaking; and (e) receptive vocabulary size could uniquely predict the lexical dimension of L2 speaking. The results are interpreted in order to provide a range of pedagogical implications.